Analysis of the Influence of Fundamental and External Factors on Stock Prices in Mining Sector Companies Listed on the Indonesia Stock Exchange. Issue 4 (2021) - Putra, Andri Setia; Adam, Mohamad; Widiyanti, Marlina; Wahyudi, Tertiarto
No abstract available